Progressivity of in vitro resistance of Klebsiella pneumoniae ESBL to meropenem and amikacin therapy in specimens from the intensive care unit of Saiful Anwar Hospital, Malang - Tri Irmawati, Anistia (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Introduction: Multidrug-resistant organism (MDRO) infections pose a significant global health challenge. The WHO has identified Klebsiella pneumoniae as a high-priority pathogen responsible for such infections. The presence of K. pneumoniae ESBL can lead to higher mortality rates. Currently, antibiotics like meropenem and amikacin are used to treat K. pneumoniae ESBL infections. However, there is no existing research on how antibiotic resistance develops over time. This study aimed to investigate the progression of in vitro resistance of K. pneumoniae ESBL to meropenem and amikacin in samples from the ICU at Saiful Anwar Hospital. Methods: This study uses the AZDZST method, a novel technique called the Ameri-Ziaei double antibiotic synergism test for assessing antimicrobial synergy. It functions as a disk diffusion test designed for double antibiotic synergy, with inhibition zone diameters providing data similar to other disk diffusion methods. This makes AZDAST simple to perform using the Kirby-Bauer disk susceptibility test. The method is independent and does not require reference tables like CLSI guidelines. Results are interpreted by comparing inhibition zone sizes around single and dual disks; a reduction in zone size indicates resistance. Klebsiella pneumoniae ESBL isolates, confirmed by Vitek 2, were tested for susceptibility to meropenem and amikacin. These isolates were exposed to 10 µg meropenem disks, 30 µg amikacin disks, and a combination of both disks using AZDAST over 14 days. The inhibition zones were measured after 18-24 hours of incubation at 37°C. Results: Amikacin antibiotics exhibited resistance by the fifth day of exposure, while meropenem showed resistance on the 12th day across three samples, and on the 14th day in one sample. The combination of amikacin and meropenem also exhibited resistance by day 14 of exposure. There was no significant difference in the duration of resistance between monotherapy and the combination therapy of meropenem and amikacin. Conclusion: Meropenem shows resistance by day 12, while amikacin is resistant from day 5. There is no significant difference in resistance duration between monotherapy and combination antibiotic treatments against Klebsiella pneumoniae ESBL in vitro.